Long-Term Voluntary Physical Exercise Exerts Neuroprotective Effects and Motor Disturbance Alleviation in a Rat Model of Parkinson’s Disease - Wan-Ling Tsai; Hsin-Yung Chen; Ying-Zu Huang; Yuan-Hao Chen; Chi-Wei Kuo; Kai-Yun Chen; Tsung-Hsun Hsieh (Behavioural Neurology)
Background. Parkinson’s disease (PD) is the second most prevalent neurodegenerative disorder affecting 7–10 million individuals. The pathologic hallmark of PD is nigrostriatal dopaminergic neuron loss, leading to several motor and nonmotor disturbances, such as akinesia, gait disturbance, depression, and anxiety. Recent animal studies have demonstrated that physical exercise improves behavioral and neuropathological deficits in PD. However, the exact underlying mechanism underlying this effect remains unclear. In this study, we investigated whether long-term exercise has neuroprotective effects on dopaminergic nigrostriatal neurons and whether it further alleviates impairment of the gait pattern, locomotor activity, akinesia, and anxiety-like behavior in PD rats. Methods. A hemiparkinsonian rat model, generated by unilateral injection of 6-hydroxydopamine (6-OHDA) into the medial forebrain bundle, was applied to evaluate neuroprotective effects and motor behaviors. Comprehensive spatiotemporal gait analysis, open-field locomotor activity, akinesia, apomorphine-induced rotational analysis, and dopaminergic neuron degeneration level were assessed every week and up to 8 weeks after daily voluntary running wheel exercise. Results. Compared with the sham-treated group, we found that 10 weeks of voluntary exercise (i.e., 2-week exercise before PD lesion and 8-week exercise post-PD lesion) significantly reduced 6-OHDA-induced motor deficits in the gait pattern, akinesia, and rotational behavior in the exercise group. Immunohistochemically, a tyrosine hydroxylase-positive neuron in the substantia nigra was significantly preserved in the exercise group. Conclusions. Our results demonstrated that long-term exercise training is effective for neuroprotection and further attenuates motor declines induced by 6-OHDA in an experimental model of PD. Our data further highlighted potential therapeutic effects of long-term physical exercise relevant to clinical effects for further potential application on human PD subjects.